2011
DOI: 10.1021/ie1018639
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Competitive Adsorbates on the Catalytic Properties of PtSnNaMg/ZSM-5 Catalysts for Propane Dehydrogenation

Abstract: This paper is aimed at studying the influence of the competitive adsorbates (HCl, lactic acid, and citric acid) on the structural and catalytic properties of PtSnNaMg/ZSM-5 catalysts for propane dehydrogenation. N 2 adsorption, X-ray diffraction, inductively coupled plasma, NH 3 temperature-programmed desorption, H 2 temperature-programmed reduction and transmission electron microscopy were applied for characterization of the prepared catalysts. The catalytic performance was tested in a microreactor. The obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…However, traditional methods, such as steam cracking and fluid catalytic cracking, do not meet the market need for propene and its derivatives. , Therefore, catalytic propane dehydrogenation has been considered to be an attractive production route, which can be simply classified into direct propane dehydrogenation (PDH) and oxidative dehydrogenation of propane (ODHP). Yet, so far, the latter has not been applied to industrial production, although it would provide some advantages, such as decreased coke deposition and circumvention of thermodynamic equilibrium constraints. , Instead, direct PDH has been realized industrially mainly with Pt- and Cr-based catalysts. Considering the high cost of Pt-based catalysts and the pollution problems associated with Cr-based catalysts, as well as their deactivation issues, V-based catalysts may provide potential alternatives for PDH. , …”
Section: Introductionmentioning
confidence: 99%
“…However, traditional methods, such as steam cracking and fluid catalytic cracking, do not meet the market need for propene and its derivatives. , Therefore, catalytic propane dehydrogenation has been considered to be an attractive production route, which can be simply classified into direct propane dehydrogenation (PDH) and oxidative dehydrogenation of propane (ODHP). Yet, so far, the latter has not been applied to industrial production, although it would provide some advantages, such as decreased coke deposition and circumvention of thermodynamic equilibrium constraints. , Instead, direct PDH has been realized industrially mainly with Pt- and Cr-based catalysts. Considering the high cost of Pt-based catalysts and the pollution problems associated with Cr-based catalysts, as well as their deactivation issues, V-based catalysts may provide potential alternatives for PDH. , …”
Section: Introductionmentioning
confidence: 99%
“…Continuous removal of hydrogen through a membrane can overcome the equilibrium‐limited conversion to allow milder reaction conditions to be used. Hence, side reactions can also be suppressed and coke formation reduced or even avoided . Modelling of propane dehydrogenation by using a membrane‐supported platinum catalyst (Pt, Sn/Mg(Al)O), and Pd−Ag and Pr−Cu alloy CMs, showed that the pressure should not exceed 5 bar at a temperature of 250 °C to avoid catalyst coking.…”
Section: Catalytic Membranes (Cms)mentioning
confidence: 99%
“…Propylene is one of the raw materials for the synthesis of polymers such as acrylic acid, polypropylene, polyacrylonitrile, and propylene oxide in the petrochemical industry. The two main ways to obtain propylene are derived from the oil stock by steam and catalytic cracking of naphtha. Recently, compared with traditional methods, catalytic propane dehydrogenation (PDH) shows advantages in propylene yield and operating cost. , Furthermore, owing to the increased production of shale gas worldwide and uncertainty of future oil prices, PDH including oxidative PDH (OPDH) and nonoxidative PDH is regarded as an alternative to produce propylene.…”
Section: Introductionmentioning
confidence: 99%